Manual de procedimientos para la mejora de gestión del área de alimentos y bebidas del Hotel Poseidón. - Cusme Cevallos, Richard Fernando (2018)
The objective of the research is to design a hotel procedure manual to improve the management of food and beverages at the Poseidón Hotel of Manta Canton, Manabí Province. The information collected was obtained through bibliographic review and field work, being an exploratory-descriptive process. Regarding the results, in the first phase the characteristics in the food and drink area of the Poseidón Hotel, mission, vision, structure and organization chart were identified. In the second phase, the operative procedures in the area of food and beverages were diagnosed, applying tools such as, interview, internal analysis, direct interview; allowing to identify existing problems, such as not implementing the appropriate methods that help improve management, in addition to not having a structure and flowcharts on process maps addressed to the internal client at the time of performing the tasks in the area under study; the work performance of the employees was analyzed, detecting deficiencies based on the quality of the hotel management aligned with the INEN norms on the manipulation of food and beverages. In the third phase, the manual of procedures, definition and analysis of the information, design and structure of the manual and objectives of the area were drawn up. In conclusion, the procedures manual was prepared allowing the organization of activities and processes in the food and beverage areas of the Poseidón Hotel.